Parabiblica Coptica - Miroshnikov, Ivan (Parabiblica, 2023)
"The present volume focuses on the Coptic parabiblical texts - those texts that do not belong to the Bible but fall in its orbit - which include not only the Apocrypha but also the works of the Apostolic Fathers. The contributions deal with a wide range of topics and literary genres, including apocryphal acts and the so-called apostolic memoirs. The volume is divided into two sections: editiones, which contains editions of several important texts in Sahidic Coptic, and studia, which comprises five articles on Coptic parabiblical literature. The literary works discussed in the volume are contextualized in the scope of Coptic literature, regardless of whether they were originally composed in Coptic or translated into Coptic from Greek. Some of the contributions also deal with the reception of Coptic literature in Arabic and Old Nubian literary traditions." --